Teachers’ Expectancy and Students’ Attitude towards Science - Prihadi Kususanto; Chin Sook Fui; Lim Hooi Lan (Journal of Education and Learning (EduLearn), 2012)
The main purpose of this study was to investigate the influence of teachers’ expectancy and students’ attitude towards science (ATS). The participants were 130 teachers and 300 students from secondary schools in Indonesia. The results indicated teachers’ expectancy significantly affected students’ ATS. Different kind of expectancy led teachers to have different classroom behavior. Teachers expect students from the science streams to have significantly higher potential to improve their academic achievements compared to the students from non-science stream. The results also showed that there is a significant correlation between teachers’ expectancy and students’ perception of teachers’ behavior. Furthermore, because students from science stream perceived that their teachers are supportive, they believe that the teachers expected them to score higher in science. In turn, this belief led them to possess higher ATS compared to the non-science stream students, which perceived that their teachers are focusing more on controlling their behavior. It could be concluded that teachers’ expectancy affected students’ ATS, moderated by the students’ perception of teachers’ behavior.